Peran Ibu dalam Perspektif Islam terhadap Pencegahan Stunting pada Anak Usia Dini - Ridwan, Ridwan; Slamet, Slamet (MOMENTUM : Jurnal Sosial dan Keagamaan, 2025)
This study aims to analyze the role of mothers from an Islamic perspective in preventing stunting among early childhood in Banyuwangi Regency. Stunting is a chronic nutritional problem that remains a serious challenge in Indonesia, including in Banyuwangi, with the national stunting prevalence reaching approximately 21.5%. In the Islamic context, mothers hold a central position as madrasah al-ūlā (the first school) for their children, being responsible not only for education and moral development but also for ensuring adequate nutrition and child health. This research employs a qualitative approach with a descriptive method, conducted in several districts in Banyuwangi Regency by involving mothers with young children, religious leaders, and health workers. Data were collected through in-depth interviews, observation, and documentation, then analyzed thematically. The findings indicate that the role of mothers in preventing stunting is strongly influenced by religious understanding, health education, and social environmental support. Islamic values such as the recommendation to breastfeed, maintaining cleanliness, the consumption of halalan ṭayyiban food, and spiritual awareness are proven to contribute to shaping healthy family lifestyles. Thus, it can be concluded that the Islamic perspective provides a strong normative and moral foundation in efforts to prevent stunting. Strengthening the role of mothers through religious guidance, family education, and cross-sector collaboration based on Islamic values is a strategic step toward building a healthy, intelligent, and morally upright generation in Banyuwangi Regency.